Når musikken gir mening. - Wagle Christensen, Torild (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
As the title of this treatise indicates, the topic is communication about quality. The author explores the general possibilities and limits of linguistic communication regarding the quality of grade school concerts, with specific concerts as her observational data. The crucial question is where to draw the line between what can be expressed verbally and what cannot when it comes to communicating about quality in this context. The point of departure for the author's exploration is the noticeable tension that exists between different participants in The Cultural Rucksack (DKS) initiative and the school concert arena. Other researchers have explored this issue, but their contributions do not converge regarding the level of tension and the content of the different stances (cf. Borgen & Brandt 2006; Breivik & Christophersen 2014; Holdhus 2014). When Music Makes Sense aims particularly at clarifying the latter question, i.e., illuminating the specific content of the different stances. The lines of conflict and accord are made more apparent and palpable, and previous research is partly amended. This applies notably to the pupils own opinions on quality, as the treatise shows that they have more divergent opinions than what had been noted in previous research on DKS.